Structural dynamic of the annual ryegrass from defoliation to seeds harvest - Lübke Bonow, Joice Fernanda; Pereira da Cunha, Ricardo; Mittelmann, Andréa; de Marco Flório, Diego; Bohn, Alberto; da Silva Pedroso, Carlos Eduardo (Revista Ceres, 2023)
The aerial part distribution and arrangement can significantly affect the forage resource’s use, both for the leaves and seeds harvesting. This work aimed to verify the structure derived from different times of pasture use and the subsequent seeds production in a long-cycle ryegrass cultivar. Weekly assessments of number and length of living leaves, elongation of the internodes, tillering, plants’ height, structural components (leaf, stem, flower, and dead material), seeds yields components, and seeds yield, to determine the pasture structure along its production cycle. The ryegrass cv BRS Ponteio pasture had its structure significantly modified just after 150 days (thermal sum: 1303 degrees-days) from seeding without the defoliation. Defoliation during the vegetative period did not alter the plants’ structure until the seeds’ production. Defoliation just after the beginning of the internodes’ elongation caused a significant tillering growth, which maintained the high seeds production potential, without plants lodging, besides promoting a more significant leaves harvesting. Subsequent pasture use determined predominant stems and flower harvesting, compared to the leaves, and the significant reduction of the production seeds and potential seeds production.